Multitasking roles of the mammalian deacetylase SIRT6 - Hassanieh, S; Mostoslavsky, R (Academic Press, 2018)
Sirtuins (SIRT) are highly conserved proteins first described as nicotinamide adenine dinucleotide (NAD+)-dependent type III histone deacetylases. They are the mammalian homologs of the SIR2 gene found in yeast. Seven homologs (SIRT1–7) have been described, all sharing an NAD+ binding catalytic domain comprising 275 amino acids and variable N and C termini. This difference in their terminal domains dictates distant roles and cellular localization of the members of the sirtuin family. In this review, we will focus on the chromatin deacetylase SIRT6, a multitasking protein with various roles in metabolism, development, DNA repair, and cancer. We will provide current knowledge in the context of its structure, enzymatic activity, and regulation. We will discuss its role in genomic stability and DNA repair, metabolism, and development. Finally, we will review SIRT6’s involvement in several diseases.